LEXICAL FEATURES OF ARABIC LANGUAGE IN MEDICAL TERMINOLOGY - Kodirova , Aziza (Oriental Journal of Philology, 2025)
The medical language, with a rich history, has developed further with the globalization of medicine and scientific collaboration. This article analyzes the main issues related to the translation of medical terminology in the Arabic language. Medical terms, their meanings, and the lack of clarity in their translation, as well as cultural and linguistic differences, homonymy, and polysemy, are challenges that translators must address. These problems demand a deeper exploration of medical terms and translation issues. The article also discusses Arabic medical words and terms, their historical development, and their impact on modern medical translation.